2020
DOI: 10.3390/w12082248
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Risk Perception of Water Quality and Its Influencing Factors between Lay People and Factory Workers for Water Management in River Sosiani, Eldoret Municipality Kenya

Abstract: This study evaluates the differences between risk predictors and risk perception regarding water pollution. Specifically, it focuses on the differences in risk perception between factory workers and lay people situated in textile industries near the River Sosiani in Eldoret, Kenya. The lay people are divided into two groups. The respondents living downstream are situated mostly in town centers and at the mid/lower parts of the river, and the respondents living upstream are mainly found at the upper parts of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 83 publications
5
26
0
Order By: Relevance
“…A sense of unease may be particularly meaningful in those who cannot purchase bottled water, which is deemed safer, and are bound to consume tap water because of their poor economic possibilities. Indeed, people with lower socio-economic status are more likely to perceive water pollution as a problem because water quality is an issue of immediate concern due to their struggles to meet their basic needs [47,48]. Instead, risk perception is attenuated when participants consider precautions and sanitation procedures adopted at the community level as effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A sense of unease may be particularly meaningful in those who cannot purchase bottled water, which is deemed safer, and are bound to consume tap water because of their poor economic possibilities. Indeed, people with lower socio-economic status are more likely to perceive water pollution as a problem because water quality is an issue of immediate concern due to their struggles to meet their basic needs [47,48]. Instead, risk perception is attenuated when participants consider precautions and sanitation procedures adopted at the community level as effective.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, risk perception is attenuated when participants consider precautions and sanitation procedures adopted at the community level as effective. In this regard, previous research has demonstrated that risk perceptions are negatively correlated with acceptance and benefit perceptions of sanitation systems [49], as well as with the general trust in the government's capacity to manage water pollution through wastewater treatment [48]. It is thus possible that believing that sanitation procedures are effective contributes to alleviating anguish and fear of being poisoned by polluted water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have shown that contamination with fecal bacteria may not only occur due to unsanitary hygiene practices of people handling the dispenser machines but also through the attrition of pipes and corrosion. These problems may be contributing factors not only to bacterial contamination but may also lead to contamination by toxic chemicals (Ebrahim et al 2015;Yau et al 2016;Mumbi & Watanabe 2020). Leakage and cross-contamination between sewage pipes and drinking water pipelines or may be due to leaky and worn out pipes may be one reason for this contamination.…”
Section: Discussionmentioning
confidence: 99%
“…17 To evaluate the amount of public engagement and the required positive behavioral response, it is necessary to gain a deeper understanding of how the general public feels about water quality and its importance for environmental sustainability. [18][19][20][21][22][23][24][25][26] To implement and evaluate the success of water quality improvement plans and water pollution management strategies, policymakers must take a more in-depth look at a variety of factors, including human factors such as perception, knowledge, awareness, communication, and societal fabric, as well as economic factors, especially in light of socio-economic impact and climate change. 27 It is more challenging for developing countries with limited resources to provide potable water.…”
Section: Introductionmentioning
confidence: 99%